Incidental findings during computed tomographic angiography diagnostic work-up in patients with arteriogenic erectile dysfunction - Jan Schönhofen; Vignes Mohan; Martin C. Schumacher; Markus Bechir; Hak H. Keo; Heinz Schönhofen; Thomas Joder; Curt Diehm; Christoph Kalka; Nicolas Diehm (Swiss Medical Weekly, 2019)
AIM